IMPROVING STUDENTS’ WRITING SKILL THROUGH ROUND TABLE TECHNIQUE - Aseptiana Parmawati; Iman Santoso; Yana Yana (Eltin Journal : Journal of English Language Teaching in Indonesia, 2020)
In Writing for General Communication course, students are expected to be able to write using several genres of text. In reality, most of the students in second semester at IKIP Siliwangi face some problems related to writing skill. To improve the students’ writing skill, the lecturers need to find out an appropriate technique for the students. This research used Classroom Action Research (CAR). The objectives of the study are: 1) finding out whether or not Round Table can improve the students’ writing skill 2) finding out classroom situation when Round Table implemented in writing for general communication course. The finding was supported by the result of students’ writing scores. The average score of pre test was 68.31. After the implementation of Round Table Technique in every cycle, the students’ speaking score were getting better. It can be seen from the result of students’ average score 75.15 in cycle 1 and 81.5 in cycle 2. It can be concluded that Round Table Technique can improve students’ speaking skill and improve speaking classroom into a better situation. Keywords: Writing Skill, Round Table Technique, CAR